The incompatibility of the vision of God as a basis of factual belief from philosophical perspective - Indriaty Ismail (Universiti Kebangsaan Malaysia, 2012)
Religious people may feel confident that they have something that nonreligious people lack, namely, direct experience of God. They may claim that such religious experience, like visions of God, is a way of knowing God’s existence. This claim has been examined by some scholars and philosophers in the field of philosophy of religion. The purpose of this writing is to analyze the reasonableness of believing in the existence of God on the basis of this claim. The methodological approach of gathering data is mainly through document analysis on various books of philosophy of religion and philosophy of God. This writing concludes that visions lack the consistency and predictability needed to form the basis of any factual belief.